2015
DOI: 10.1016/j.jmbbm.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of tissue microstructure and functionality during freezing by modulation of cytoskeletal structure

Abstract: Cryopreservation is one of the key enabling technologies for tissue engineering and regenerative medicine, which can provide a reliable long-term storage of engineered tissues (ETs) without losing their functionality. However, it is still extremely difficult to design and develop cryopreservation protocols guaranteeing the post-thaw tissue functionality. One of the major challenges in cryopreservation is associated with the difficulty of identifying effective and less toxic cryoprotective agents (CPAs) to guar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 73 publications
1
15
0
Order By: Relevance
“…Alterations in cell and tissue properties associated with freezing are generally associated with the physical processes involving water such as ice formation or dehydration that can affect cellular integrity and structures such as the extracellular matrix and its associated proteins [13][14][15]. Similar observations were made in a study by Ternifi et al [16] that reported a large drop in the elastic modulus of kidney tissues that were subjected to freezing.…”
Section: Resultsmentioning
confidence: 53%
“…Alterations in cell and tissue properties associated with freezing are generally associated with the physical processes involving water such as ice formation or dehydration that can affect cellular integrity and structures such as the extracellular matrix and its associated proteins [13][14][15]. Similar observations were made in a study by Ternifi et al [16] that reported a large drop in the elastic modulus of kidney tissues that were subjected to freezing.…”
Section: Resultsmentioning
confidence: 53%
“…Since fibrils are connected via branching points, the model yields connections that appear to be in a bent configuration ( Fig. 2(d)) [30]. Thus, the parameter-based model mimics the tortuous collagen fibrils as shown in many SEM images.…”
Section: Methodsmentioning
confidence: 78%
“…In addition, this study showed that other imaging techniques, such as the SEM, produce more accurate feature size or diameter. Along those lines, we recently measured the fibril diameter of rat tail collagen (monomer-based collagen) as 101.6 nm using SEM [30]. Based on those results, an additional group with 100 nm-sized diameters was included to the parameter-based model to examine the effect of fibril diameter on permeability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the formation of ice crystals may alter collagen integrity, this alteration has only been observed in engineered biomaterials. 19,20 This suggests that native tendon and ligament are unaffected by the ice crystals, especially when carefully frozen. We preserved fascicles by freezing the whole rat tail with its skin intact without freezing the isolated individual fascicles, and placing fascicles in plastic bags, wrapped in PBS-soaked gauge.…”
Section: Discussionmentioning
confidence: 99%